Treatment and outcomes in pediatric inflammatory myofibroblastic tumors – A systematic review of published studies - Raitio, Arimatias (Academic Press, 2025)
Inflammatory myofibroblastic tumor (IMT) is a soft tissue neoplasm which can be locally invasive, recur, or in rare cases metastasize. Often originating from the abdomen or thorax, IMT most commonly affects children and young adults. Due to its rarity comprehensive reports detailing clinical management and outcome(s) are sparse and often based on limited index case numbers. This study systematically analyzes outcome metrics of pediatric IMT and identifies risk factors for mortality. Medline/Embase databases were searched in accordance with PRISMA guidelines. Final analysis included 57 studies with 673 IMT patients (355 males, 53%). Individual patient data was available for 405 cases with a median follow-up period of 36 months. Tumor sites included abdomen/pelvis (n=233, 58%), thorax (n=125, 31%), head/neck (n=34, 8%), and extremities (n=13, 3%). Surgical tumor resection was the mainstay of treatment, while only 20 patients (5%) were treated non-operatively. Recurrence(s) were reported in 80 patients (20%) with 34 (12%) requiring reoperation. Positive tumor margins were a significant risk factor for tumor recurrence (p<0.0001). Chemo/radiotherapy was reported in 98 patients (25%). Most patients (94%) survived; 81% (n=237) with no evidence of recurrent disease, 14% (n=41) were alive with disease, and 25 (6%) died of disease. Positive margins at primary operation, and metastatic disease were associated with mortality (p<0.0001 for both). IMT is a rare tumor with favorable outcome for the majority of patients. Whilst most patients will present with benign tumors, complete surgical resection (R0) is crucial, as positive surgical margins are a significant risk factor for tumor recurrence and mortality.